X-chromosome-wide profiling of MSL-1 distribution and dosage compensation in Drosophila - Legube, Gaëlle (Cold Spring Harbor Laboratory Press, 2006)
In Drosophila, dosage compensation is achieved by a twofold up-regulation of the male X-linked genes and requires the association of the male-specific lethal complex (MSL) on the X chromosome. How the MSL complex is targeted to X-linked genes and whether its recruitment at a local level is necessary and sufficient to ensure dosage compensation remain poorly understood. Here we report the MSL-1-binding profile along the male X chromosome in embryos and male salivary glands isolated from third instar larvae using chromatin immunoprecipitation (ChIP) coupled with DNA microarray (ChIP–chip). This analysis has revealed that majority of the MSL-1 targets are primarily expressed during early embryogenesis and many target genes possess DNA replication element factor (DREF)-binding sites in their promoters. In addition, we show that MSL-1 distribution remains stable across development and that binding of MSL-1 on X-chromosomal genes does not correlate with transcription in male salivary glands. These results show that transcription per se on the X chromosome cannot be the sole signal for MSL-1 recruitment. Furthermore, genome-wide analysis of the dosage-compensated status of X-linked genes in male and female shows that most of the X chromosome remains compensated without direct MSL-1 binding near the gene. Our results, therefore, provide a comprehensive overview of MSL-1 binding and dosage-compensated status of X-linked genes and suggest a more global effect of MSL complex on X-chromosome regulation.